Postoperative Port Site Complications of Patient Undergoing Laparoscopic Cholecystectomy - Ahmad, Jamshid; Shah, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Laparoscopic cholecystectomy is the standard surgical treatment for symptomatic gallstones. Despite being minimally invasive, port site complications such as pain, infection, and abscess can occur and may affect recovery and satisfaction. Objective: To determine the frequency of postoperative port site complications of patients undergoing laparoscopic cholecystectomy at Hayatabad Medical Complex, Peshawar. Methods: This study was conducted on a sample of 172 patients aged 18 to 65 years undergoing laparoscopic cholecystectomy for symptomatic gallstones. Patients with uncontrolled diabetes, uncontrolled hypertension, or chronic liver and kidney disease were excluded. Postoperative port site complications were evaluated within 30 days, such as pain, infection, and abscess. SPSS 21 was used for data analysis. Associations were assessed using the chi-square test, with P values significant at ≤ 0.05. Results: The mean age of 172 patients in the present study was 42.30 ± 14.32 years. Gender-wise, females had a higher majority at 75.6%. Postoperative port site complications were infection, observed in 13 (7.6%) cases, pain in 11 cases (6.4%), and abscess in 4 cases (2.3%). No statistically significant associations were found between the complications and demographic factors. Conclusion: Laparoscopic cholecystectomy is a safe procedure with minimal port site complications, such as infection (7.6%), pain (6.4%), and abscess (2.3%).